STRATEGI KOMUNIKASI MAL SKA PEKANBARU DALAM MEMPUBLIKASIKAN SKA FAMILY CARD KEPADA PENGUNJUNG - Mardhatillah, Riska; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Based on the data that researchers get from mall SKA Pekanbaru, the number ofvisitors who came into SKA Family Card decreased each year. From the year 2010,there were 1167 people joined in SKA Family Card. Then in 2011 decreased up to 972people who joined in SKA Family Card next year, up to 607 people who had gatheredin SKA Family Card. Objective of this study was to determine the strategy message, thestrategy of public and media strategies used in the dissemination of Mal SKAPekanbaru cards for family visitors.This research uses descriptive qualitative, and techniques of data collection areclassified through observation, interviews, and documentation. Informans in this studytotaled 9 people taken based on accidental and purposive sampling. Models ofinteractve data analysis researchers use to decribe research results in technical dataanalysis to verify the validity of data and research using participatory extensiontechniques and triangulation.The result about the communication strategy of mall SKA Pekanbaru aboutstrategy audience is people at Pekanbaru with middle class and above. Media used byMall SKA Pekanbaru is print media like Riau Pos, Tribun Pekanbaru, Pekanbaru Posdan Metro Riau, social media like facebook and twitter, sms broadcast and print mediacampaign like banner and flyer. Contents of the messages used in the publishing SKAfamily Card is informative and persuasive messages. Several contributing factors is thecompany’s commitment in all promotional programs, many visitors who come everydayand many are conducting transactions at the mall SKA Pekanbaru. Factor that do notsupport is the very low level of tenant participation in promotional programs.Keywords : Strategy, Communication, Publication